2011
DOI: 10.1007/s00423-011-0823-6
|View full text |Cite
|
Sign up to set email alerts
|

The versatility of the pedicled vertical rectus abdominis myocutaneous flap in oncologic patients

Abstract: VRAM flaps are reliable tools for defect coverage in the oncologic patient to prevent chronic ulceration, lymphangitis or more severe complications like septic rupture of femoral vessels and hip disarticulation. Donor site morbidity is tolerable, and patients' satisfaction is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 44 publications
(48 reference statements)
1
51
0
10
Order By: Relevance
“…Abdominal hernias after TRAM and VRAM are the most significant morbidity, with an incidence rate of about 13% of the cases (49,54). Free muscle flaps may be indicated if local muscle group have been resected, previously injured or irradiated (3).…”
Section: A B a Bmentioning
confidence: 99%
“…Abdominal hernias after TRAM and VRAM are the most significant morbidity, with an incidence rate of about 13% of the cases (49,54). Free muscle flaps may be indicated if local muscle group have been resected, previously injured or irradiated (3).…”
Section: A B a Bmentioning
confidence: 99%
“…Preoperative chemotherapy and radiotherapy did not affect early morbidity. Sunesen et al (13) higher than the level reported by other investigators (10,17). No late morbidity due to incarceration was observed, and the abdominal brace that was provided was not used continuously by many of the patients.…”
Section: Resultsmentioning
confidence: 81%
“…Although free flaps play an important role in the management of these defects in otherwise healthy patients, they may require longer operation durations and overburden patients in critical condition, such as those with progressive malignant disease. In these situations, sufficient soft tissue coverage needs to be achieved by simple and reliable techniques with moderate donor site morbidity (10).…”
Section: Discussionmentioning
confidence: 99%